Perbandingan Fuzzy Time Series Chen dan Cheng untuk Peramalan Harga Beras di Kabupaten Banyumas - Sari, Dian Kartika; Sa'adah, Aminatus (Universitas Negeri Gorontalo, 2024)
Indonesia is mostly an agricultural country. Most people here make a living from farming. Rice is a major crop in Indonesia. The price of rice is very important to the economy, especially in farming areas like Banyumas. Fluctuating rice prices can affect the economic lives of both farmers and consumers in the region. The rapid fluctuation in rice prices and the uncertainty of future prices demand the need for rice price forecasting. This study uses fuzzy time series to forecast rice prices. The prediction models used are the Chen model and the Cheng model. To calculate the accuracy of the models, MAPE calculations are employed. Based on the results, the MAPE value for the Chen model is 0.957539%, and for the Cheng model, it is 0.477921%. The results indicate that the accuracy of the Cheng model is higher than that of the Chen model, meaning that the Cheng model is better suited for forecasting rice prices in Banyumas Regency.